2018
DOI: 10.1542/peds.2017-4310
|View full text |Cite
|
Sign up to set email alerts
|

Medical Marijuana for Minors May Be Considered Child Abuse

Abstract: The Food and Drug Administration categorizes marijuana (cannabis) as a Schedule I drug, meaning that it has no currently accepted medical use, a high potential for abuse, and no good data on safety. Other Schedule I drugs are heroin, lysergic acid diethylamide, peyote, methaqualone, and 3,4-methylenedioxymethamphetamine ("ecstasy"). The authors of some studies have shown that marijuana can reduce nausea and vomiting from chemotherapy, can improve food intake in patients with HIV, can reduce neuropathic pain, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…After participating in a medical simulation curriculum for acute pediatric cannabis intoxication, pediatric emergency medicine trainees reported increased confidence in identifying and managing THC exposures in pediatric patients ( Burns et al, 2018 ). A medical education article examined the ethics around reporting a caregiver to child protective services (CPS) for providing their child marijuana edibles for therapeutic reasons without consulting a medical professional ( Hines et al, 2018 ). Emergency medicine nurses participating in focus groups about perceived changes in workload due to cannabis legalization were concerned about spikes in pediatric cannabis intoxication cases, which they attributed to edibles ( Wolf et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After participating in a medical simulation curriculum for acute pediatric cannabis intoxication, pediatric emergency medicine trainees reported increased confidence in identifying and managing THC exposures in pediatric patients ( Burns et al, 2018 ). A medical education article examined the ethics around reporting a caregiver to child protective services (CPS) for providing their child marijuana edibles for therapeutic reasons without consulting a medical professional ( Hines et al, 2018 ). Emergency medicine nurses participating in focus groups about perceived changes in workload due to cannabis legalization were concerned about spikes in pediatric cannabis intoxication cases, which they attributed to edibles ( Wolf et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, several information sources in this review conceptualized cannabis intoxication as child abuse, with calls for CPS involvement (Pelissier et al, 2014), even in jurisdictions where it had been legalized (Thomas et al, 2018;Murti, 2017;Bergeron et al, 2017;Friedman et al, 2017;Heard et al, 2017) and without discussion of broader implications and potential harms of CPS involvement. (Hines et al, 2018) Given the documented history of racism and overrepresentation of Black and Indigenous families in CPS systems in North America (Denison et al, 2014;Child Welfare Information Gateway, 2016) and persistent racism in health care (Mahabir et al, 2021), blanket recommendations for CPS involvement in all cases of cannabis intoxication may impact families decisions to seek care for their children in the case of acute cannabis intoxication (Pelissier et al, 2014). However, this concern is impossible to evaluate in the current literature because of the very small number of information sources in this review that reported race or ethnicity.…”
Section: Clinical Management and Guidancementioning
confidence: 99%
“…Yet with some research showing benefits of cannabis, there exists a counterbalancing literature cautioning against the use of cannabis, 52 particularly in the neonatal period. 53,54 Some have even suggested that treating minors with cannabis “may be considered child abuse.” 55 Few can argue that further research elucidating the benefits or consequences of cannabis for specific disease states through well-designed RCTs that include pediatric populations is needed. The National Academies report, however, acknowledges the barriers to cannabis research—regulatory (eg, being Schedule I), cannabis supply (eg, access to research product), and funding limitations—as well as methodological challenges that inhibit gold standard RCTs from taking place.…”
mentioning
confidence: 99%